Opioid analgesic use among patients with kidney disease: a systematic review - Shania Liu; Megan B. Sands; Jack W. Kerferd; Sanam Fathabadi; Kok Eng Khor; Chin Hang Yiu; Katelyn Phinn; Matthew A. Anderson; Grace Redmayne; Kenneth Yong; Jonathan Penm (Karger Publishers, 2024)
Introduction: Opioid analgesics are often used to manage moderate to severe pain. A significant proportion of patients taking opioids have compromised kidney function. This systematic review aimed to examine the available evidence on the safety and analgesic effect of opioid use in adults with kidney disease. Methods: We searched eight electronic databases from inception to 26th January 2023. Published original research articles in English reporting on opioid use and pharmacokinetic data among adults with reduced renal function were included. Article screening, data extraction, and quality assessment were conducted by at least two investigators independently. This review was registered prospectively on PROSPERO (ID: CRD42020159091). Results: There were 32 observational studies included, 14 of which reported on morphine use, three involved fentanyl use, two involved hydromorphone use and 13 articles reported on other opioids including codeine, dihydrocodeine, and buprenorphine. Conclusion: There is limited and low-quality evidence to inform the safety and analgesic effect of opioid use in reduced renal function. Morphine remains the opioid for which there is the most evidence available on safety and analgesic effect in the context of renal disease. Greater caution and consideration of potential risks and benefits should be applied when using other opioids. Further high-quality studies examining clinical outcomes associated with the use of different opioids and opioid doses in renal disease are warranted.